Movement of “Natural Parenting” as (as if) a Confrontation with a Consumer Society - Diomidova, Alla; Makarova, Viktoria (Respectus Philologicus, 2014)
The article describes the movement of natural parenting and its confrontational ideology. The authors sought to provide a general understanding of the movement natural parenting and describe its confrontational ideology. Speaking in terms of sociology, sling parents form the imagined community and this particular ideology is the focus of the presents study. The hypothesis of the study lies in the assumption that discourse analysis of natural parenting is to discover traits of propaganda discourse. The subject of the analyzed discourse is set critically in relation to the modern practice of consumption, declares the personal position free from stereotypes and willingness to confront the dictatorial influence of consumer values on the style of parenting. The subject is prone to reflection and the generation of ideological texts. Despite the fact that natural parenting has positioned itself as anti-consumer-orientated, it creates a consumer niche of the “right” products for children. Being against some commodities, natural parenting creates demand for the other ones. Sling clothing for Moms (sling jackets), accessories and the like become the accompanying sling commodities. Natural parenting has positioned itself as focused on the child’s needs. The traditional educational discourse is marked as providing the convenience for a mother who does not love her child. Many of the arguments of the sling discourse are based on fear to fail to meet a child’s needs (or to cause harm to hishealth, to threaten hislife), which relates it with the mainstream advertising discourse.